Potential mesenchymal stem cell therapeutics for treating primary biliary cholangitis: advances, challenges, and perspectives - Yang, Yanlei; Zhao, Robert Chunhua; Zhang, Fengchun (Frontiers in Cell and Developmental Biology, 2022)
Primary biliary cholangitis (PBC) is a cholestatic autoimmune liver disease characterized by the gradual destruction of small intrahepatic bile ducts that eventually leads to liver cirrhosis, failure, and even carcinoma. The treatment options for PBC are limited: The main treatment choices are the US Food and Drug Administration-approved ursodeoxycholic acid and obeticholic acid. However, many patients fail to respond adequately to these drugs and the adverse effects frequently lead to low life quality. For patients with end-stage PBC, liver transplantation remains the only effective treatment. Given their low immunogenicity, prominent immunomodulation property, differentiation potential, and tissue maintenance capacity, mesenchymal stem cells (MSCs) are emerging as new options for treating liver diseases, including PBC. Accumulating evidence from basic animal research to clinical studies supports the positive effects of MSC-based therapy for treating PBC. In this review, we characterize the underlying roles and mechanisms of MSCs for treating liver diseases and highlight recent basic and clinical advances in MSC-based therapy for treating PBC. Finally, the current challenges and perspectives for MSC-based therapy in clinical application are discussed, which could help accelerate the application of MSCs in clinical practice, especially for refractory diseases such as PBC.